Application of non-automated Lean strategies for quality improvement in manual assembly processes: a case study in the white goods industry. - Fu-López, Jayling Selena; Fierro Aguilar, Jaime Patricio; Rodríguez-Flores, Fernando Raúl; Duque-Aldaz, Francisco Javier (Ingeniería Química y Desarrollo, 2025)
Quality management in manual manufacturing processes represents a recurrent challenge in industrial plants without automation, especially in developing countries. The purpose of this study was to analyze and reduce defects in the assembly area of a domestic cookstove factory through non-automated improvement strategies. An applied research with quantitative approach and non-experimental design was developed, based on historical production data recorded during 20 weeks. Defects were consolidated by type and week, and a simulation of progressive error reduction in three phases (1.5 %, 2 %, 3-4 %) was applied. Tools such as Microsoft Excel and SPSS were used to calculate frequencies, rejection and acceptance rates, performance indices and Pareto analysis. Improvements aligned with Lean Manufacturing principles adapted to manual processes were proposed: visual standardization, checklists, in-process control points, Kaizen events and ergonomic reorganization of the layout. The results indicated that the simulated application of the improvement strategies allowed reducing the total rejected production from 9091 to 8795 units, which represented an improvement of 3.25 %. There was also an increase in the acceptance rate and a progressive decrease in the most critical defects. Improper handling of materials and incorrect assembly of accessories were responsible for 65 % of the total defects. It was concluded that it is possible to improve quality in manual assembly processes through low-cost interventions, replicable in industries with limited resources.
Keywords: Manual Assembly; Defect Reduction; Lean Manufacturing; Process Improvement; Quality Control; Non-Automated Production